From Cognition to Behavior: Associations of Workplace Health Culture and Workplace Health Promotion Performance With Personal Healthy Lifestyles - Chang, Yao-Tsung; Tsai, Feng-Jen; Yeh, Ching-Ying; Chen, Ruey-Yu (Frontiers in Public Health, 2021)
Introduction: The aim of this study was to explore associations of workplace health culture and workplace health promotion (WHP) performance with employees’ healthy lifestyles and health statuses. Methods: In total, 27 enterprises and 1732 participants were recruited in Taiwan for a cross-sectional-designed questionnaire survey. WHP performance was measured by the Workplace Health Scorecard, and it was filled out by the person responsible for promoting WHP in each workplace. Results: Workplace health culture was significantly related to WHP performance, healthy lifestyles, and health statuses. In particular, the peer support domain was significantly related to healthy behaviors and may illustrate the importance of establishing peer support to promote healthy behaviors. Conclusions: Building a good workplace health culture should be taken seriously, and more studies exploring associations of health culture and WHP performance with employee health are needed.